Impacts of obesity, maternal obesity and nicotinamide mononucleotide supplementation on sperm quality in mice. Issue 2 (August 2019) - Youngson, Neil A; Uddin, G Mezbah; Das, Abhirup; Martinez, Carl; Connaughton, Haley S; Whiting, Sara; Yu, Josephine; Sinclair, David A; Aitken, R John; Morris, Margaret J
Abstract : Male fertility and sperm quality are negatively impacted by obesity. Furthermore, recent evidence has shown that male offspring from obese rat mothers also have reduced sperm quality and fertility. Here, we extend work in this area by comparing the effects of both maternal obesity and offspring post-weaning diet-induced obesity, as well as their combination, on sperm quality in mice. We additionally tested whether administration of the NAD + -booster nicotinamide mononucleotide (NMN) can ameliorate the negative effects of obesity and maternal obesity on sperm quality. We previously showed that intraperitoneal (i.p.) injection of NMN can reduce the metabolic deficits induced by maternal obesity or post-weaning dietary obesity in mice. In this study, female mice were fed a high-fat diet (HFD) for 6 weeks until they were 18% heavier than a control diet group. Thereafter, HFD and control female mice were mated with control diet males, and male offspring were weaned into groups receiving control or HFD. At 30 weeks of age, mice received 500 mg/kg body weight NMN or vehicle PBS i.p. for 21 days. As expected, adiposity was increased by both maternal and post-weaning HFD but reduced by NMN supplementation. Post-weaning HFD reduced sperm count and motility, while maternal HFD increased offspring sperm DNA fragmentation and levels of aberrant sperm chromatin. There was no evidence that the combination of post-weaning and maternal HFD exacerbated the impacts in sperm quality suggesting that they impact spermatogenesis through different mechanisms. Surprisingly NMN reduced sperm count, vitality and increased sperm oxidative DNA damage, which was associated with increased NAD + in testes. A subsequent experiment using oral NMN at 400 mg/kg body weight was not associated with reduced sperm viability, oxidative stress, mitochondrial dysfunction or increased NAD + in testes, suggesting that the negative impacts on sperm could be dependent on dose or mode of administration.